Extended-Field Irradiation and Intracavitary Brachytherapy Combined With Cisplatin and Amifostine for Cervical Cancer With Positive Para-Aortic or High Common Iliac Lymph Nodes: Results of Arm II of Radiation Therapy Oncology Group (RTOG) 0116. Issue 7 (1st October 2011) - Small, William; Winter, Kathryn; Levenback, Charles; Iyer, Revathy; Hymes, Sharon R.; Jhingran, Anuja; Gaffney, David; Erickson, Beth; Greven, Kathy
Abstract : Objectives: Radiation Therapy Oncology Group (RTOG) 0116 was designed to test the ability of amifostine (Ethyol; MedImmune LLC, Gaithersburg, MD), a cytoprotective agent, to reduce the acute toxicity of combined therapy with extended-field irradiation, brachytherapy, and cisplatin chemotherapy in patients with cervical cancer with para-aortic or high common iliac disease. This report presents the results of part 2. Materials and Methods: Radiation Therapy Oncology Group 0116 was a 2-part trial. Part 1 delivered extended-field irradiation, brachytherapy, and cisplatin; part 2 added amifostine and required 16 evaluable patients to assess an improved toxicity profile. Eligibility included evidence for high common iliac or para-aortic metastasis. Patients were treated for a total dose of 45 Gy in 25 fractions with intracavitary irradiation. Intensity-modulated radiation therapy was not allowed. The final point A dose was 85 Gy low-dose rate equivalent. High-dose rate techniques were allowed. The positive para-aortic and iliac nodes were to be boosted to 54 to 59.4 Gy. Amifostine at 500 mg was to be delivered with every fraction of radiotherapy. Results: The study opened on August 1, 2001, and closed March 3, 2007, after accruing 45 patients, 18 for the second part with amifostine. This analysis reports the primary end point for the patients entered on part 2 of the study. Three patients were excluded, one was ineligible, and 2 withdrew. The median follow-up was 22.9 months (range, 6.5-45.4 months). The median dose of amifostine delivered was 5000 mg (range, 500-13, 500 mg). Thirteen patients (87%) experienced an acute grade 3/4 toxicity (excluding grade 3 leukopenia). This compared to an 81% rate in part 1 of the trial. The estimated median survival was 34.8 months with a 20% late grade 3/4 toxicity rate. Conclusions: Amifostine, as delivered in this study, did not reduce acute toxicity in this patient population.